Licensing policy and platform models of telemedicine: A multi-case study from China - Wang, Zhong; Xu, Rui; Liu, Yan; Li, Yiming (Frontiers in Public Health, 2023)
Introduction As a form of platform economy, telemedicine is not growing as fast as other digital platforms. The existing literature seldom pays attention to how licensing policy affects the development of telemedicine platform models. Methods This paper uses the method of multi-case study and the theory of policy implementation as mutual adaptation to research the influence mechanism of telemedicine platform licensing policy on the platform model in China. Results The findings of the current study are as follows: (1) three models can be classified in accordance with different platform providers in China: medical institution platform, Internet company platform and local government platform; (2) bargaining power, reputation mechanism and resource specificity are important dimensions in the analysis of platform models; (3) as an implementer in the process of licensing policy, the platform provider can not only directly determine the establishment and formation of platform model but also indirectly affect the sustainable development of platform model by affecting the supplier and the demander of platform; and (4) The impact between licensing policy and platform model is dynamic and bidirectional, mainly exerted via administrative orders, market-oriented mechanism and medical insurance. Conclusions The research enlightens practical exploration in telemedicine and enriches the theoretical innovation in platform.